2011
DOI: 10.1007/s11104-011-0785-z
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal symbiosis on serpentine soils: the effect of native fungal communities on different Knautia arvensis ecotypes

Abstract: Serpentine soils represent a unique environment that imposes multiple stresses on vegetation (low Ca/Mg ratios, macronutrient deficiencies, elevated heavy metal concentrations and drought). Under these conditions, a substantial role of arbuscular mycorrhizal (AM) symbiosis can be anticipated due to its importance for plant nutrition and stress alleviation. We tested whether serpentine and non-serpentine populations of Knautia arvensis (Dipsacaceae) differ in the benefits derived from native AM fungal communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
1
16
0
1
Order By: Relevance
“…Our previous studies (Słomka et al, 2011b) indicated that V. lutea from either the Vosges or Sudeten mountains were non-mycorrhizal or, at best, poorly colonized. In Albania, all violets examined, except of V. albanica, were strongly mycorrhizal, even at altitudes above 2000 m. The degree of AMF colonization was not increased by stress upon growth in serpentine soil or in culture experiments (Stevanović et al, 2010;Doubková et al, 2011). However, the degree of colonization and arbuscule formation must not be directly correlated with the extent of metabolic activities of the AMF-plant symbiosis.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our previous studies (Słomka et al, 2011b) indicated that V. lutea from either the Vosges or Sudeten mountains were non-mycorrhizal or, at best, poorly colonized. In Albania, all violets examined, except of V. albanica, were strongly mycorrhizal, even at altitudes above 2000 m. The degree of AMF colonization was not increased by stress upon growth in serpentine soil or in culture experiments (Stevanović et al, 2010;Doubková et al, 2011). However, the degree of colonization and arbuscule formation must not be directly correlated with the extent of metabolic activities of the AMF-plant symbiosis.…”
Section: Discussionmentioning
confidence: 88%
“…In the case of field scabious (Knautia arvensis), serpentine populations showed a significant lower AMF colonization than plants from non-polluted sites (Doubková et al, 2011), although the degree of AMF colonization of a plant does not generally correlate with its fitness above a threshold value of about 20% colonization (Feldmann et al, 2009). Worldwide, some serpentine violets, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced elemental concentrations in leaves, result from different mechanisms, including the sequestration of most trace elements in the roots, restricting uptake and transport to the shoots (Baker 1981) and influences of soil microbe (Doubková et al 2011). Any such mechanism failed only for Zn at Palmerton because concentrations in leaves are at least ten times higher than in others sites, suggesting a potential break point or critical level of Zn in soil where homeostasis breaks down.…”
Section: Discussionmentioning
confidence: 99%
“…Khusus peran fitoremediasi, jenis ini dilaporkan berpotensi sebagai jenis fitoremediasi untuk unsur Fe, Mn, Cu, dan Zn pada konstruksi lahan basah air asam tambang (Tuheteru et al 2016) dan Hg (Ekamawanti et al 2014) (Joner & Leyval 1997;Tseng et al 2009;Redon et al 2009; Andrade et al 2009), mengurangi (Vivas et al 2005;Amir et al 2013;Husna et al 2016) serta tidak ada pengaruh (Galli et al 1995) (Guo et al 1996), pucuk Trifolium repens (Vivas et al 2006), akar Costularia comosa (Lagrange et al 2011, Knautia arvensis (Doubková et al 2011), dan Alpitonia neocaledonica dan Cloezia artensis …”
Section: Pendahuluanunclassified